2011
DOI: 10.1038/modpathol.2010.237
|View full text |Cite
|
Sign up to set email alerts
|

Improved demonstration of immunohistochemical prognostic markers for survival in follicular lymphoma cells

Abstract: Follicular lymphoma (FL) is one of the most common forms of the low-grade non-Hodgkin's lymphoma in adults, with a characteristic translocation, t(14;18)(q32;q21) that deregulates the expression of the BCL2 gene. The clinical course of FL patients is variable, whereby a subset of patients survive for long periods even without relapses, whereas the majority have frequent relapses with shorter survival. We have analyzed a series of 186 FLs, studying the correlation between clinical outcome and the tumor cell exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
0
11
2
1
Order By: Relevance
“…Camacho et al 41 also found worse survival in follicular lymphoma cases with higher expression of MDM2. 41 It is important to state that this study is not based on cases with uniform and standardized treatment, and includes patients treated with different protocols, reflecting the absence of any standard approach to the treatment of follicular lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Camacho et al 41 also found worse survival in follicular lymphoma cases with higher expression of MDM2. 41 It is important to state that this study is not based on cases with uniform and standardized treatment, and includes patients treated with different protocols, reflecting the absence of any standard approach to the treatment of follicular lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…The use of polymerase chain reaction (PCR) tests for detecting B cell clonality in follicular lymphoma is associated with a high rate of false negatives, due to ongoing somatic immunoglobulin variable region heavy chain (IgVH) hypermutations [22]. In addition to morphological and immunohistochemical studies, fluorescence in situ hybridisation (FISH) is the preferred method to detect the t(14;18)(q32;q21) chromosomal translocation, which is most specifically found in follicular lymphoma [23,24]. FISH analysis may have a great differential diagnostic impact, separating follicular lymphoma from reactive follicular hyperplasia and from lymphomas other than follicular lymphoma.…”
Section: Diagnosismentioning
confidence: 99%
“…Phenotypically, it is well known that FL display striking inter- and intratumoral heterogeneity in terms of the expression of several FL markers including immunoglobulin heavy chain (IgH), CD10, CD20 and BCL2 proteins. 1, 2, 3, 4 Genetically, copy number variation and exome sequencing studies have shown marked intratumoral clonal diversity within the FL. 5,6 Analysis of intratumoral clonal diversity within FL cases has shown that the IgH-BCL2 t(14;18) translocation is a founder event at the top of the hierarchy of FL oncogenic events, whereas other mutations such as those in CREBBP , MLL2 and TNFRS14 genes are acquired only by a fraction of the cells during tumor evolution.…”
Section: Introductionmentioning
confidence: 99%